The 2007 Professor John Eggleston Memorial Lecture Learning to Design: Investigating the ‘Inner Activity’ of the pupil. - Welch, Malcolm (Design and Technology Education: An International Journal, 2007)
This paper will address five questions that emerge from the title of the Design and Technology Association Education and International Research Conference 2007: ‘Linking Learning’: (a) How can we think about learning so that it informs our work in design and technology? (b) What is known about design and designing that might help pupils learn to think in a designerly way? (c) What do we know about the ‘inner activity’ of designers that can support pupils learning to design? (d) What does the pupil need to learn in order to think in a designerly way? and (e) What do we know about ‘linking learning’ and how can this inform our work in design education? The paper begins with a review of learning, one of education’s central concepts. This is followed by a discussion of the term ‘design’, the knowledge required by a designer, and how a designer comes to know. The third section of the paper examines the meaning of the term ‘design’ in the context of design and technology classrooms. The fourth section (a) discusses transfer theory of learning, and (b) identifies a variety of ‘links’ that have possible meaning for design education. The paper concludes with suggestions for approaches to research in design education. Throughout the paper, questions that could serve as the basis for both short and longitudinal research studies are identified.